2019
DOI: 10.1021/acs.jpcc.9b00686
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Active Triazine–Thiadiazole-Based p-Type Copolymer with Stable Photoelectrochemical Behavior in Acidic Electrolytes

Abstract: Design and development of visible-light-active electrode materials with efficient charge separation and enhanced stability are the main criteria for solar energy conversion in photoelectrochemical devices. Herein, we report a new metal-free photoactive polymer containing thiadiazole and triazine units with a stable photo-electroactivity in strong acidic electrolytes. The reactivity of chloro groups in cyanuric chloride and the nucleophilic substitution with 2,5-dimercapto-1,3,5-thiadiazole favors the facile (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…More details about the positions of Raman peaks can be found in the Supporting Information. 33,34 3.2. Resistive Switching by DC and AC Measurements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More details about the positions of Raman peaks can be found in the Supporting Information. 33,34 3.2. Resistive Switching by DC and AC Measurements.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the protonation effect can improve the photoelectroactivity of the Poly(DMcT-CC) polymer. 33,35 IS measurements carried out on these devices show a single semicircle in both the biases. The model circuit and fitting of IST measurements are presented in the Supporting Information Figure S6e.…”
Section: Mechanism For Resistive Switchingmentioning
confidence: 92%
See 2 more Smart Citations
“…p-Type semiconductors can function as photocathodes, and they interact with electron acceptors instead of electron donors, efficiently resisting the reductive agents and photocorrosion . Recently, the p-type semiconductors have attracted more and more attention in the development of cathodic PEC sensors. Polymer compounds such as triazine–thiadiazole-based copolymers, arylacetylene-based copolymers, and polythiophene exhibit p-type semiconductor properties, with promising applications in energy conversion and active photocathodes . Covalent organic polymers (COPs) are porous polymer compounds with the characteristics of large specific surface area, good stability, adjustable function, and controllable structure and have been widely applied in drug delivery, , catalysis, gas storage/separation, sensing, and energy storage .…”
mentioning
confidence: 99%